Floristic Diversity of Dhamrai Upazila of Dhaka With Emphasis on Medicinal Plants - Rahman, M Oliur; Antara, Rumana Tanjin; Begum, Momtaz; Hassan, Md Abul (Bangladesh Journal of Botany, 2012)
A total of 263 angiosperm species under 210 genera and 79 families have been recorded from Dhamrai Upazila of Dhaka district. Of these, Magnoliopsida is represented by 200 species under 154 genera and 62 families while Liliopsida is represented by 63 species under 56 genera and 17 families. Asteraceae is the largest family in Magnoliopsida represented by 17 species, and Poaceae is the largest family in Liliopsida represented by 20 species. Habit analysis shows that herbs, shrubs and trees are represented by 166, 23 and 74 species, respectively. Sixty two medicinal plants have been documented with their uses for the cure of more than 30 diseases, and some of these are diabetes, jaundice, diarrhoea, dysentery, spleen and liver complaints, chronic ulcers, bronchitis, rheumatism, irregular menstruation, piles, urinary problems and heart diseases. Threats to the species have also been assessed and appropriate conservation measures suggested. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11085 Bangladesh J. Bot. 41(1): 71-85, 2012 (June)